Perancangan Sistem Informasi Monitoring Persediaan Perangkat Laboratorium Ilmu Pengetahuan Alam (Studi Kasus: SMAN 22 Kabupaten Tangerang) - Rawinda Maulia; Rinna Rachmatika (CV. Multi Kreasi Media, 2023)
The Science Laboratory is a facility provided by SMAN 22 Tangerang Regency which is used for practical natural science learning for students. So that the teaching and learning activities of students and teachers do not experience difficulties, the science laboratory assistant does maintenance every day. One of the maintenance methods used is by checking each unit of equipment. The process of checking and monitoring is considered less than optimal because it has not utilized the information system. so that this makes it difficult for laboratory assistants because the assistants only hold on to a list of inventory data written on paper that is prone to being lost and scattered. This difficulty is also felt by the head of the laboratory when asking for all inventory lists as monitoring material. So we need an information system that can help make it easier for laboratory assistants in terms of recording inventory lists and the head of the laboratory can monitor the status of the ready or non-ready laboratory in real time and also the head of the laboratory can find out the track record of the performance of the semester laboratory assistant.